Effective treatment of disseminated superficial actinic porokeratosis with chemical peels – customary treatment for a rare disease. (2nd October 2020) - Lang, Berenice M.; Peveling-Oberhag, Adriane; Zimmer, Sebastian; Wegner, Joanna; Sohn, Anna; Grabbe, Stephan; Staubach, Petra
Abstract: Background: Disseminated superficial actinic porokeratosis (DSAP) is a rare dermatologic disorder of the epidermis. Often misdiagnosed as chronic UV-damage or actinic keratoses, patients are treated for years with different therapeutic options with little success. Current treatment options include imiquimod, ingenol mebutate, cryosurgery, photodynamic therapy and topical or systemic therapy with retinoids. Since those approaches show only little success or come along with major side effects, therapeutic alternatives are strongly requested. Methods: We report a series of five female patients with history of DSAP that were successfully treated with chemical peels. Results: All patients suffered from the disease for 14.4 years on average and all were refractory to at least two therapeutic options, mostly imiquimod and topical tretinoin. Patients were treated with glycolic acid 50% and salicylic acid 25% in a two-layer-technique. After a mean of three cycles every 6 weeks a clear reduction in lesion was assessed by physicians. Patients were highly satisfied with outcome and rare occurrence of side effects as assessed by TSQM questionnaire. Conclusion: Chemical peels are safe and well tolerated treatment options for patients with refractory porokeratosis. As characteristic for chronic diseases, frequent repetition of treatment is needed in order to control disease activity.